2007
DOI: 10.1016/j.cgh.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori BabA Expression, Gastric Mucosal Injury, and Clinical Outcome

Abstract: Background & Aims-The blood group antigen binding adhesin (BabA) has been proposed to play a role in disease pathogenesis. This hypothesis is based on the functional BabA status as determined by polymerase chain reaction (PCR) analysis to distinguish functional babA2 genes from nonfunctional babA1 genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 36 publications
(80 reference statements)
4
101
0
5
Order By: Relevance
“…The authors hypothesized that the poly(A) sequences between the -10 and the -35 sites could be prone to slippage mutations that allow changes in the level of transcription of downstream genes. However, other studies could not confirm that the -10 to -35 spacing played an important role in regulating babA expression [30,31] . Further studies will be necessary to fully interrogate the roles of transcriptional regulation of BabA.…”
Section: Transcriptional Regulation Of Babamentioning
confidence: 82%
See 4 more Smart Citations
“…The authors hypothesized that the poly(A) sequences between the -10 and the -35 sites could be prone to slippage mutations that allow changes in the level of transcription of downstream genes. However, other studies could not confirm that the -10 to -35 spacing played an important role in regulating babA expression [30,31] . Further studies will be necessary to fully interrogate the roles of transcriptional regulation of BabA.…”
Section: Transcriptional Regulation Of Babamentioning
confidence: 82%
“…The sequence of these two genes differed only by the presence of a 10 bp deletion in the signal peptide sequence of babA1 that eliminates its translational initiation codon. However, my group recently found that all 80 strains from a panel of Western and East Asian isolates contained an intact ATG start codon in the babA gene [31] , and another group also reported the absence of the babA1 type deletion [11,12,29,30,32] . Overall, the absence of a translation initiation codon, as described for babA1 from CCUG17875, should be rare.…”
Section: Regulation Of Babamentioning
confidence: 99%
See 3 more Smart Citations